Heat transfer and pressure drop of water based hybrid Al2O3:SiO2 nanofluids in cooling plate of PEMFC - Muhammad Syafiq, Idris; Irnie Azlin, Zakaria; Wan Azmi, Wan Hamzah (Akademi Baru, 2021)
A Proton Electrolyte Membrane fuel cells (PEMFC) is considered to be a viable alternative to Internal Combustion Engines (ICEs) in automotive applications due to the key advantages in thermal management system. The main duty of thermal management system is to maintain the desirable temperature, with a uniform temperature distribution across the stack and its individual membranes. In this paper, the thermal enhancement for two types of PEMFC cooling plates were analysed and presented. The hybrid Al?O?:SiO? was used as coolant in distributor cooling plate. The study focuses on water based 0.5% volume concentration of single Al?O? , single SiO? nanofluids, hybrid Al?O?:SiO nanofluids with mixture ratio of 10:90 and 50:50. The effect of different ratios of nanofluids to heat transfer enhancement and fluid flow in Reynold number range of 400 to 2000 was observed. A 3D computational fluid dynamic (CFD) was developed based on distributor cooling plates using Ansys 16.0. Positive heat transfer enhancement was obtained where the 10:90 Al?O?:SiO? nanofluids has the highest heat transfer coefficient as compared to other nanofluids used. However, all nanofluids experienced higher pressure drop. Therefore, the advantage ratio was used to analyze the effect of both heat transfer enhancements and pressure drop demerits for nanofluids adoption. The results concluded that 10:90 Al?O?:SiO? hybrid nanofluid is the most feasible candidate followed by 50:50 Al?O?:SiO? Al?O? hybrid nanofluids up to fluid flow of Re1000. The positive results implied that hybrid Al?O?:SiO? nanofluids do improve the single nanofluids behaviour and has a better potential for future applications in PEMFC thermal management.